Efficacy of the Developmental Trauma and Attachment Program in a residential setting. (10th January 2022) - Lenz, A. Stephen; Buckwalter, Karen Doyle; Pester, Danielle A.; Green, Kelly; Reed, Debbie
Abstract: This evaluation inspected the degree of symptom improvement associated with the Developmental Trauma and Attachment Program for decreasing symptoms of posttraumatic stress disorder (PTSD) among youth in residential treatment following complex trauma scenarios associated with domestic and international adoption/foster care. Participants were 61 youth ( M age = 13.23 years) who were predominately born in the United States ( n = 41) with 20 identifying with international domiciles. Results indicated statistically significant decreases in symptoms from admission to discharge associated with medium‐effect sizes across PTSD symptoms. Nearly one in three participants reported clinically significant changes associated with treatment, whereas two in five reported improvements but not in the clinically significant range. Female participants reported greater decreases in negative cognitions; however, no other differences in treatment response based on participant characteristics were detected. Limitations of the generalization of findings and recommendations for future researchers are provided.